Taá¹bÄ«q al-Madkhal al-Ittiá¹£ÄlÄ« fÄ« Taâ€™lÄ«mi TafsÄ«r al-Qur'Än bimaâ€™had al-JihÄd li al-BanÄt Surabaya: ØªØ·Ø¨ÙŠÙ‚ Ø§Ù„Ù…Ø¯Ø®Ù„ Ø§Ù„Ø§ØªØµØ§Ù„ÙŠ ÙÙŠ ØªØ¹Ù„ÙŠÙ… ØªÙØ³ÙŠØ± Ø§Ù„Ù‚Ø±Ø¢Ù† Ø¨Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø¬Ù‡Ø§Ø¯ Ù„Ù„Ø¨Ù†Ø§Øª Ø³ÙˆØ±Ø§Ø¨Ø§ÙŠØ§ - Kunti Nadiyah Salma; Laili Mas Ulliyah Hasan; Khowarizmi Abdul Karim; Abdul Wahab Rosyidi; Uril Bahruddin (TADRIS: Jurnal Pendidikan Islam, 2021)
Learning the interpretation of the Qur'an more precisely on thematic interpretation material, still faces obstacles in the field, including not being able to produce output that can use interpretation well. The purpose of this research is to understand: (1) the application of a communicative approach in learning interpretation of Qur’an at Al Jihad Islamic Boarding School Surabaya for female, (2) the obstacles faced by teachers in applying a communicative approach in learning interpretation of Qur’an at Al Jihad Islamic Boarding School Surabaya fro female. This research uses a qualitative approach with a descriptive type of research. Research data were collected through interviews, observation, and documentation. Data analysis was carried out using Miles and Huberman's model, are: (1) data collection, (2) data reduction, (3) data presentation, (4) concluding. The results showed that the application of the communicative approach through several steps, there are: short dialogues, exercises, questions, communicative expressions, analysis and concluding, then evaluation. And also there several obstacles in the application of the communicative approach, it is: the lack of confidence in students in expressing the results of thematic interpretations orally in Arabic, there are difficulties in developing the delivery of some material into a communicative approach, and the last is the lack of time available for learning interpretation of holy Qur’an. The conclusion of this study shows that a communicative approach is needed in learning interpretation of holy Qur’an on thematic interpretation material to be more effective.